TELAAH KRITIS IMPLEMENTASI PEMBIAYAAN MURABAHAH PADA LEMBAGA KEUANGAN SYARIAH BERDASARKAN KDPPLKS - Sugeng Widodo; Nuhbatul Basyariah (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2020)
Murabaha financing dominates the portion of Indonesia's national banking financing. Some financing models that exist in Islam and offered by Islamic banking shows the development of Murabaha financing is increasing, and several other types of Islamic banking financing go down and disappear from the financial statements of Islamic banking financing. This article aims to review and analyze the practice of Murabaha financing in Indonesian Islamic banking, and answer the concept and application of Murabaha financing is purely Islamic banking financing or replication of conventional banking credit ?. Based on the analysis of sample transaction models, Murabahah financing implementation has not been following sharia-compliant transaction definitions and criteria according to KDPPLKS where the Murabahah price structure does not contain the appropriate selling price element, but the formula for determining the selling price uses conventional credit/loan patterns.